MITIGASI RESIKO USAHA PAKAIAN BEKAS: (Penyuluhan Pada Mahasantri Pesantren Tahfidz Madinatul Quran Kota Depok) - Puspa Rini; B. Wisman S. Siregar; Kampono I. Yulianto; John Freddy (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
Business and selling are alternative solutions for alumni of the Tahfidz Islamic Boarding School, one of which is a recycled clothing fashion brand which can be done without a long process. In addition to the variations of the models that are very diverse and in accordance with the desires of young people's self-confidence, used clothes are relatively affordable. In fact, due to its